Legal Protection of Nursing Students in Implementing Clinical Practices at the Hospital - Moh Syamsul Arifin; Levina Yustitianingtyas (Universitas Negeri Semarang, 2020)
The procurement of health personnel is carried out through higher education in the health sector which is directed at producing quality health personnel in accordance with professional service standards. The Field Learning Practice stage is also known as the clinical learning process which is fully implemented in the practical field, namely the hospital under the supervision of the clinical supervisor. In carrying out student clinical practice errors or omissions may occur. The purpose of this study is to determine the responsibility of nursing students who make mistakes that result in harm to patients and to find out legal protection for nursing students who make mistakes that cause harm to patients. The research described is normative research using primary, secondary and tertiary legal materials, analytical descriptive research characteristics, legal material collection is done by document study techniques, data are analyzed qualitatively. The results show that the management of nursing student responsibilities who make mistakes can be seen from the civil aspects of the criminal and administrative aspects while the legal protection is regulated in Law Number 36 of 2009 concerning Health, Law Number 44 of 2009 concerning Hospitals, Law RI Law No. 38 of 2014 concerning Nursing, Law No. 36 of 2014 concerning Health Workers, and Regulation of the Minister of Health No. 148 of 2010 concerning Licensing and Implementation of Nursing Practices while the Cooperation Agreement between Educational Institutions and Health Institutions already contains 4 elements, namely consent of the will, authority ), specific (achievement) objects and objectives of the agreement.